2021
DOI: 10.2459/jcm.0000000000001254
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial adipose tissue may predict new-onset atrial fibrillation in patients with ST-segment elevation myocardial infarction

Abstract: Aims In this study, we aimed to determine the relationship between EAT thickness in patients with STEMI who underwent primary percutaneous coronary intervention (pPCI) and the development of new-onset atrial fibrillation during hospital follow-up. Material and methods Four hundred and thirteen consecutive patients [284 men (69%) and 129 women (31%)] with a mean age of 59 ± 11 years diagnosed with STEMI were included in this study. Atrial fibrillation de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The following variables, thought to be clinically relevant, were included in the PS model: age, body mass index, hypercholesterolemia, hypertension, Smoke status, diabetes, family history of premature coronary artery disease, prior MI, prior PCI or coronary bypass, anterior STEMI, shock at presentation, cardiac arrest at presentation, radial access, use of glycoprotein IIb/IIIa inhibitors, left main artery as infarcted related artery, multivessel disease, stent implantation, postprocedural TIMI flow grade = 3, symptom-to-balloon time, creatinine levels, LVEF. Posthoc interaction analyses between gender and the following variables were also performed: age, diabetes, anterior STEMI, symptoms-to-balloon time and multivessel disease 15,16 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following variables, thought to be clinically relevant, were included in the PS model: age, body mass index, hypercholesterolemia, hypertension, Smoke status, diabetes, family history of premature coronary artery disease, prior MI, prior PCI or coronary bypass, anterior STEMI, shock at presentation, cardiac arrest at presentation, radial access, use of glycoprotein IIb/IIIa inhibitors, left main artery as infarcted related artery, multivessel disease, stent implantation, postprocedural TIMI flow grade = 3, symptom-to-balloon time, creatinine levels, LVEF. Posthoc interaction analyses between gender and the following variables were also performed: age, diabetes, anterior STEMI, symptoms-to-balloon time and multivessel disease 15,16 …”
Section: Methodsmentioning
confidence: 99%
“…Posthoc interaction analyses between gender and the following variables were also performed: age, diabetes, anterior STEMI, symptoms-toballoon time and multivessel disease. 15,16 We also evaluated the association between LVEF and gender by means of multiple linear regression adjusting for the PS.…”
Section: Introductionmentioning
confidence: 99%
“…Those with higher EAT quantifications had increased odds of MI (OR, 2.63 [95% CI, 1.39–4.96]; I 2 =74%; P =0.003) and coronary revascularization (OR, 2.99 [95% CI, 1.64–5.44]; I 2 =70%; P <0.001; Table 2). In addition, 3 studies 47–49 (n=1031) were included for the analysis of atrial fibrillation. Individuals with higher EAT quantifications had increased odds of developing atrial fibrillation (adjusted OR, 4.04 [95% CI, 3.06–5.32]; I 2 =0%; P <0.001).…”
Section: Resultsmentioning
confidence: 99%
“…For example, some included studies measured EAT thickness at endsystole, 32,41,42 while others measured it at end-diastole. 43,47 Some averaged EAT thickness values from multiple TTE views 41,46 while others only used a single view. 47,53 Several used the average thickness over 3 cardiac cycles 42,45 while others considered 10 cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, numerous clinical and experimental studies in recent years have suggested that pericardial fat and atrial fibrosis are strongly associated with the incidence, maintenance and recurrence of atrial fibrillation in patients managed with the rhythm-control strategy 5,6 and also in patients with ischemic cardiomyopathy. 7 The heart is surrounded by a variable amount of perivisceral adipose tissue. 8 It consists of a paracardial component, placed outside of the visceral pericardium, and an epicardial component placed between the visceral pericardium and epicardium, and combined they make pericardial fat.…”
Section: Introductionmentioning
confidence: 99%